Analisis Kebijakan Peraturan Daerah Yang Mengandung Materi Muatan Ajaran Islam Di Kota Palembang - Kiki Mikail (Tamaddun: Jurnal Kebudayaan dan Sastra Islam, 2018)
This research is analytical descriptive research. This study places policy analysis and as the main and free variable that will influence the process of establishing a Regional Regulation as a dependent variable. In article 5 of the Republic of Indonesia Constitution states that the regional government has the right to determine regional regulations or other regulations in order to carry out regional autonomy.The local government of Palembang has issued three local government regulations that have Islamic sharia laws, namely regional regulation number 2 of 2004 concerning the eradication of prostitution, regional regulation number 11 of 2006 concerning the prohibition of circulation and sale of alcoholic products and local regulations on zakat. in order to be right on target and more effective, some variables need to be considered by Palembang stakeholders so that the Regional Regulations that are stipulated are not just legality, but more than that it must be a general rule that all local regulations are made in order for the common good Palembang community. Keywords : Political Analys, local goverment regulations, local autonomy, the politics of sharia law